How hydrocolloids can control the viscoelastic properties of acid-swollen collagen pastes. (May 2022) - Sobanwa, M.; Foster, T.J.; Yakubov, Gleb; Watson, N.J.
Abstract: The interactions between proteins and polysaccharides are of considerable importance in the food industry. In this study, the effect of adding non-charged methylcellulose (MC), hydroxypropylmethylcellulose (HPMC), medium (GM) and high (GH) molecular weight guar gum and negatively charged sodium carboxymethylcellulose (CMC) was investigated on the rheological and thermal properties of acid-swollen collagen pastes, as a function of collagen concentration. Dynamic frequency sweeps showed that the addition of the hydrocolloids, except for CMC, increased the storage modulus (G′) and loss modulus (G″) of collagen pastes at all collagen levels investigated. MC, HPMC, GH, and GM increased the collagen pastes' storage modulus to a similar extent. In contrast, the values of the loss moduli were found to be markedly different for each hydrocolloid. The loss factor (tan δ) showed that incorporating the hydrocolloids made the pastes less elastic than pure collagen pastes. The phase transition temperature of collagen measured during the temperature sweep tests was not affected by MC, HPMC, GH, and GM. However, CMC shifted the transition temperature of collagen to higher temperatures. Micro Differential scanning calorimeter (microDSC) results showed that the presence of MC, HPMC, and guar gums did not affect the denaturation temperature (Td) and enthalpy (ΔH). In contrast, the addition of CMC increased the denaturation temperature and denaturation enthalpy of collagen pastes. By fixing the hydrocolloids' viscosifying power and changing the collagen concentration, collagen pastes with different hydrocolloids show different viscoelastic properties. Graphical abstract: Image 1 Highlights: Viscoelastic and thermal properties of collagen paste with and without hydrocolloids were studied. Charged carboxymethylcellulose weakened the collagen paste network. Incorporating uncharged hydrocolloids enhanced the collagen paste network. Charged carboxymethylcellulose increased collagen denaturation temperature. The denaturation temperature of collagen was not affected by uncharged hydrocolloids.